RADIKALISME DI JANTUNG PENDIDIKAN ISLAM - Khamami Zada (Badan Litbang dan Diklat Kementerian Agama RI, 2009)
AbstractThis paper is a critical reflection on radicalism phenomenon which emerges at the heart of Islamic education, especially at Madrasah and Islamic boarding school, which is enhanced more by its development at schools and campus. This educational institution is chosen since it it at this place the character development is begun as a cadre forming facility. The aspiration of radical Islamic group is to change a state, replace its basis as well as its law. The emerge of this radicalism has shifted Islam in Indonesia, i.e. from the one dominated by moderate-ism to radicalism. Islamic education as a people liberation facility is faced against a challenge on how to develop a moderate religious consciousness so in turn among the people will grow an inclusive understanding